Manual de Gestión Tributaria en la Empresa “Mega Constructor &GM SAS” 2021. - Calva Alejandro, Nathaly Michelle (2023)
The Curriculum Integration work called “tax management manual in the company mega constructors &GM SAS” was carried out with the purpose of designing procedures in the tax area to maintain a correct order in the presentation and declaration of taxes and annexes that the company has. The manual is a support tool that allows members and staff to increase their knowledge and tax culture, since it facilitates the understanding of the subject in general, being the initial step, to obtain better levels of compliance in declaration, presentation and payment of taxes. This manual was initiated with a general classification of the tax duties and obligations that the company has, with their respective maximum dates in accordance with the legal provisions to carry it out. Subsequently, procedures focused on compliance with tax duties and obligations were developed, with the purpose of making the company aware of the taxes they are obligated to declare, as well as annexes that they have to present in accordance with the dates established in accordance with the current regulations. Finally, flowcharts were designed for the tax process with the aim of giving a clear knowledge to the partners and staff of the company, who understands in a simple way the process to follow for the making of tax returns and the presentation of annexes. In the complementary part of the curriculum integration work, the conclusions are recorded with 3 the respective recommendations which generate a contribution to the company. Previously, the interview with the company ́s partners was conducted, in which relevant information was obtained on the level knowledge of a manual of procedures in the tax field and thus determine the current situation of the taxpayer and his environment.